International environments and practices of higher education - Caputo, Andrea; Lock, Deborah; Hack-Polay, Dieu (Emerald Publishing Limited, 2022)
Taking forward the notion of the scholar without borders, International Environments and Practices of Higher Education provides a critical review of the teaching practices in higher education in international contexts. Sticky problems and debates about inclusivity, diversity, and cultural representation in the curriculum and classroom are explored through the eyes of the academics who negotiate complex teaching landscapes either on a temporary or permanent basis. The aspiration for universal nuanced teaching practices which reflect individual and national identities, along with newly emerging global ones that represent virtual academic citizenship that cross geographical and political borders, are presented as a foundation on which to instil borderless higher education.